2019
DOI: 10.1111/bju.14797
|View full text |Cite
|
Sign up to set email alerts
|

Circulating oestrogen receptor mutations and splice variants in advanced prostate cancer

Abstract: ObjectiveTo characterize circulating oestrogen receptor (ER) mutants and splice variants in men with advanced prostate cancer. Materials and MethodsSequential blood samples were obtained from men with advanced prostate cancer, and from healthy controls. Bloodderived RNA samples were analyzed using droplet digital PCR for the presence of six ERa mutations (E380Q, L536Q, Y537C, Y537S, Y537N and D538G), and six ERa and ERb splice variants (ERa-66, ERa-36, ERb1, ERb2, ERb4 & ERb5). ResultsA total of 94 samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Markedly reduced ERβ levels can be observed in grade 4/5 carcinomas compared to that in grade 3 carcinomas ( 186 ). Five splice variants of ERα and ERβ (ERα-36, ERβ2, ERβ3, ERβ4, and ERβ5) were detected in men with and without prostate cancer ( 187 ). However, the role of ERα-36 remains unclear.…”
Section: Ers In the Manifestation Of Diseasesmentioning
confidence: 99%
“…Markedly reduced ERβ levels can be observed in grade 4/5 carcinomas compared to that in grade 3 carcinomas ( 186 ). Five splice variants of ERα and ERβ (ERα-36, ERβ2, ERβ3, ERβ4, and ERβ5) were detected in men with and without prostate cancer ( 187 ). However, the role of ERα-36 remains unclear.…”
Section: Ers In the Manifestation Of Diseasesmentioning
confidence: 99%
“…Recently, Qu et al characterized circulating estrogen receptor mutants and isoforms in men from blood-derived RNA samples that were sequentially characterized from healthy and advanced PCa patients. The authors found six ERα mutations (E380Q, L536Q, Y537C, Y537S, Y537N, and D538G) in plasma from patients with advanced PCa, and six ERα and ERβ isoforms (ERα-66, ERα-36, ERβ1, ERβ2, ERβ4, and ERβ5) ( 19 ).…”
Section: Splice Variants In the Estrogen Receptormentioning
confidence: 99%
“…Alternative splicing of ER-mRNAs leads to the existence of several splice variants of ERβ, which have different roles but are structurally similar ( Figure 1 ) [ 17 ]. For example, it has been suggested that ERβ splice variants are associated with biological behaviors such as drug resistance and apoptosis in prostate cancer [ 18 , 19 ]. Faria et al found that, in prostate cancer, ERβ2 and ERβ can induce stem cell properties of tumors as well as the development of chemoresistance.…”
Section: The Structure Of Estrogen Receptorsβ (Erβ)mentioning
confidence: 99%